Escherichia coli RIC is able to donate iron to iron-sulfur clusters. - Lígia S Nobre (PLoS ONE, 2014)
Escherichia coli RIC (Repair of Iron Centers) is a diiron protein previously reported to be involved in the repair of iron-sulfur proteins damaged by oxidative or nitrosative stresses, and proposed to act as an iron donor. This possible role of RIC was now examined specifically by evaluating its ability to donate iron ions to apo-iron-sulfur proteins, determining the iron binding constants and assessing the lability of its iron ions. We show, by UV-visible, EPR and resonance Raman spectroscopies that RIC may participate in the synthesis of an iron-sulfur cluster in the apo-forms of the spinach ferredoxin and IscU when in the presence of the sulfide donating system IscS and L-cysteine. Iron binding assays allowed determining the as-isolated and fully reduced RIC dissociation constants for the ferric and ferrous iron of 10-27 M and 10-13 M, respectively. Mössbauer studies revealed that the RIC iron ions are labile, namely when the center is in the mixed-valence redox form as compared with the (μ-oxo) diferric one. Altogether, these results suggest that RIC is capable of delivering iron for the formation of iron-sulfur clusters.